IMPLEMENTASI KBIJAKAN PENGELOLAAN COMMAND CENTER KOTA BANDUNG - Dahanny, Jasmine Sekar Ayu; Susanti, Dian (Jurnal Sosial Politik Unla, 2023)
This research is motivated by the unoptimal management of the Bandung City Command Center. Based on these problems, researchers identified the following problems: how is the Implementation of the Bandung City Command Center Management policy which has been regulated in Mayor Regulation Number 20 of 2022 concerning Command Center Governance. Based on this, this study aims to find out, analyze and describe in depth about how the Implementation of the Bandung City Command Center management policy. The theory used by researchers is the Policy Implementation model developed by Van Meter & Van Horn which consists of 6 dimensions, namely: policy size and objectives, resources, characteristics of implementing agents, dispositional attitudes of implementers, interorganizational communication and implementing activities, and the economic, social and political environment. This research uses a qualitative approach and descriptive study method. Data collection was carried out by interview, observation, documentation study and literature study. The results showed that the Implementation of the Command Center Governance Policy in Bandung City has not run optimally, this is due to several obstacles including: not having an official website page, not a Technical Implementation Unit (UPT), lack of socialization of the Command Center program to the wider community.